Didactic strategies for the development of fundamental competencies of the peruvian professional - Rodríguez del Solar, Natalia (2014)
Facing the fundamental changes of our society, our university system has to change as well fundamentally for the better pursuing the mission of putting itself at the service of the development of our country. This changes must aim at the integral development of the human being, in order to make it more productive, a teacher, a researcher and for the creating of spiritual and material wealth. We have identified the didactic strategies in order to improve and enhance the basic competencies of the peruvian university student and professional. Also identify the different “learnings” necessary for the development of competencies in order to optimize the formation of peruvian professionals for the betterment of peruvian society. We have applied different surveys to docents and students. Our research is exploratory, descriptive, aplicative and interpretative.Results: We have found and confirmed the most participative didactic strategies that facilitate the development of competencies of the peruvian professional. We have identified the different “learnings” for the development of competencies. We have found and confirmed that values are a fundamental component of competencies.Conclusions: We have identified the didactic strategies that promote the development of basic competencies of the peruvian professional. We have identified the necessary “learnings” for the development of competencies and the didactic strategies that promote them. We have recognized values as a key component of competencies. We have identified 50 values that are cultivated by applying the didactic strategies selected for the personal development of the peruvian professional and for the betterment of society.